Changes of intraocular lens position induced by Nd:YAG capsulotomy - Martin Fus (Biomedical Papers, 2022)
Aims. The aim of this study was to evaluate the changes in IOL position (axial shift, tilt and decentration) in the capsular bag after Nd:YAG laser capsulotomy and to create a user-friendly software that is optimized for the output of available imaging technology, then verify the relationship between the biometric parameters of the eye and the extent of changes in the IOL position. Patients and Methods. The study included 35 artephakic eyes that underwent laser capsulotomy. Before and at least one hour after capsulotomy, all patients underwent the following assessments: optical biometry (Lenstar LS900), OCT with anterior segment module (Optovue Avanti) and IOL photography in infrared mode using reference unit (Verion). The original software solution was designed for the graphical evaluation of the differences between centering, axial displacement and tilt of IOL. Changes in IOL position were evaluated as simple differences before and after the laser procedure and as differences in absolute values (abs). Results. The following results show the average differences in IOL position: ACD=0.02±0.23 mm (abs=0.11±0.20 mm), IOL decentration in x-axis = -0.001±0.091 mm (abs=0.065±0.063 mm), IOL decentration in y-axis =0.012±0.119 mm (abs=0.048±0.53 mm), tilt in horizontal plane TILT-H=0.11±0.83° (abs=0.51±0.66°) and tilt in vertical plane TILT-V = -0.14±0.49° (abs=0.26±0.44°). All changes were insignificant (P>>0.05). In total, 74.29% of IOLs showed a hypermetropic shift. A moderate positive correlation was found between the absolute differences in horizontal tilt and keratometry (r=0.45). Relationship with other changes and parameters were weak. Conclusion. In conclusion, the use of the original software solution developed by the authors showed that changes in IOL centering, axial displacement and tilt occur after Nd:YAG capsulotomy, but average differences were insignificant. In almost 3/4 cases, there was a hypermetropic axial displacement of the IOL.